2020
DOI: 10.1042/bsr20192095
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-197 regulates chondrocyte proliferation, migration, and inflammation in pathogenesis of osteoarthritis by targeting EIF4G2

Abstract: Recent studies have demonstrated that microRNAs (miRNAs) are involved in many pathological conditions including osteoarthritis (OA). In this study, we aimed to investigate the role of miR-197 in OA and the potential molecular mechanism. The expression levels of miR-197 was detected by quantitative real-time PCR analysis. Cell proliferation and migration abilities were performed by MTT and transwell assays. The concentrations of inflammatory cytokines, including IL-1β, IL-6, and TNF-α, were detect using ELISA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…EIF4G2 is an important mediator of translation initiation and plays an important role in the process of cell mitosis [35]. It has been reported that EIF4G2 affects chondrocyte inflammation [36]. Our study found that XIST interacted with EIF4G2 to affect the inflammatory response, and lncRNA XIST attenuated MDM2-mediated ubiquitination and degradation of EIF4G2.…”
Section: Discussionsupporting
confidence: 54%
“…EIF4G2 is an important mediator of translation initiation and plays an important role in the process of cell mitosis [35]. It has been reported that EIF4G2 affects chondrocyte inflammation [36]. Our study found that XIST interacted with EIF4G2 to affect the inflammatory response, and lncRNA XIST attenuated MDM2-mediated ubiquitination and degradation of EIF4G2.…”
Section: Discussionsupporting
confidence: 54%
“…EIF4G has two functional homologs in mammals, namely, EIF4G1 and EIF4G2 (Caron et al, 2004). EIF4G2 expression is promoted in osteoarthritis cartilage tissues, and EIF4G2 may be implicated in the pathogenesis of osteoarthritis (Gao S. et al, 2020). Nevertheless, the role of EIF4G2 in IDD remained unknown, and this study filled this gap to a certain extent.…”
Section: Discussionmentioning
confidence: 83%
“…To further determine the downstream target of miR-101-3p-mediated ECM remodeling, we conducted follow-up experiments. EIF4G2 is abnormally expressed in osteoarthritis (Gao S. et al, 2020). The binding site between miR-101-3p and EIF4G2 was predicted by using the Starbase database (Figure 4A).…”
Section: Mir-101-3p Targeted Eif4g2mentioning
confidence: 99%
“…Cell cycle research revealed that EIF4G2 silencing led to a rise in cells in the G0/G1 phase and a drop in cells in the G2/M phase (36). EIF4G2 promotes cell proliferation in a variety of tissues, such as chondrocytes and ovarian cancer (37)(38)(39). EIF4G2 has also been proven to have a strong proliferative effect on human colon cancer cells, and its expression is increased in skeletal muscle after I/R (36,40).…”
Section: Discussionmentioning
confidence: 99%